Question 421483
you start off with 6x^4 - 7x^2 = 0

factor out an x^2 to get:

x^2 * (6x^2 - 7) = 0

your factors are x^2 and 6x^2 - 7

set x^2 = 0 and you get x = +/- sqrt(0) = 0

set 6x^2 - 7 = 0

add 7 to both sides of the equation to get 6x^2 = 7

divide both sides of the equation by 6 to get x^2 = 7/6

take square root of both sides of equation to get x = +/- sqrt(7/6)

it does not appear that you needed to use the quadratic formula.

x = 0
x = + sqrt(7/6)
x = - sqrt(7/6)

6x^4 - 7x^2 = 0

when x = 0, this comes out to be equal to 0.

when x = + sqrt(7/6) this comes out to be 0.

when x = - sqrt(7/6) this also comes out to be 0.

in order to apply the quadratic equation, you would have had to factor out the x^2 first to get:

x^2 * (6x^2 - 7) = 0

you could then have applied the quadratic formula to 6x^2 - 7 = 0

since the standard form of a quadratic equation is equal to:

ax^2 + bx + c = 0

a would have been 6
b would have been 0
c would have been -7

you would then have applied the quadratic formula to that.

you would have gotten x = +/- sqrt(168)/12

sqrt(168)/12 is equivalent to sqrt(168/144) which is equivalent to sqrt(7/6).

you would have gotten the same answer either way.

x is equal to 0 or x is equal to + sqrt(7/6) or x is equal to - sqrt(7/6).